The influence of mfp-implant on tissue pertinent changes of wistar rattus-rattus - Widjijono Widjijono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Fluoride for caries prevention if consumes for a long period, it is sometimes made bored. Normally, fluoride intake is uncontrolled and cause fluorosis. Alternatively, implant fluor becomes the controlled method. Te study was aimed to determine the influence of MFP-implant on tissue pertinent changes of Wistar Rattus-rattus. The research subjects were Rattus-rattus mother of 20 rats (2 days pregnant). Twenty rats were divided into 4 groups, namely control (K), implant P1, implant P2 and implant P3. Subcutaneous implantation was done on rat back. On the 8th day, euthanasia was done. Excission was done surround the implant tissue, then blocked and fixed by formalin buffer. The specimen was cut along the implant tissue were examined by light microscope. The data were analyzed by descriptive statistic. The result showed that the incision was cured on the 5th – 7th day. Tissue pertinent changes determination showed that there was lipid cell infiltration and relatively thicker of tissue on implant P3 and. there was not any inflammation cell infiltrated and fibrous tissue. In conclusion, the infiltration of lipid cell on implant P3. The implant P2 was fulfilled the requirement of implant devices.Key words : MFP-implant, pertinent changes, rat